Material flow analysis for household waste - Sazan M. Ali; Dana K. Mawlood (Zanco Journal of Pure and Applied Sciences, 2021)
Material flow analysis (MFA) is a tool used for a sustainable quantification and assessment of matter and substances during a specific period of time. The MFA system is mathematically controlled by a simple mass balance which defines all inputs, outputs and stocks of a process. Waste management in Erbil city has become the main problem and increased the generation rate per capita per year with economic growth and changing lifestyle. The current study aims to apply MFA for household waste in Erbil city to obtain a better, systematic waste management. The process model includes all input and output flows of household wastes and it provides a better management in household waste in the city. The total import of the household waste is 1.62 ton/year that is divided into four parts which are 1.23 tons/year is for kitchen waste (organic, combustible and incombustible), 0.03 tons/year for garden waste, and 0.03 tons/year for other waste and 0.33 for stocks material.